2013
DOI: 10.1039/c3nr01025b
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal ablation cancer therapy using homogeneous CsxWO3 nanorods with broad near-infra-red absorption

Abstract: Recently, photothermal ablation therapy (PTA) employing near-infrared radiation (NIR) has been extensively investigated as an emerging modality for cancer management. However, the clinical translation of this promising approach is limited by the lack of PTA agents with broad NIR absorption, low cost and high photothermal conversion efficiency. Herein, we have developed PEGylated homogeneous CsxWO3 nanorods (a mean size ∼69.3 nm × 12.8 nm) with broad photo-absorption (780-2500 nm) as a novel NIR absorbent for P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 48 publications
3
63
0
Order By: Relevance
“…5b), which could be explained by heat diffusion or reactive oxygen species (ROS) migration induced lysosome damage and cytoskeleton protein degradation [39,40]. Our results was supported by the observation reported by P. Kalluru et al that tungsten oxide can sensitize the formation of singlet oxygen and thus cause the complete destruction of solid tumors in mice upon irradiation with 980 nm light [30]. We next checked the stability of cytoskeleton protein post laser irradiation.…”
Section: Photothermal Ablation Studies In Vitro and In Vivosupporting
confidence: 85%
“…5b), which could be explained by heat diffusion or reactive oxygen species (ROS) migration induced lysosome damage and cytoskeleton protein degradation [39,40]. Our results was supported by the observation reported by P. Kalluru et al that tungsten oxide can sensitize the formation of singlet oxygen and thus cause the complete destruction of solid tumors in mice upon irradiation with 980 nm light [30]. We next checked the stability of cytoskeleton protein post laser irradiation.…”
Section: Photothermal Ablation Studies In Vitro and In Vivosupporting
confidence: 85%
“…3a for GNR@DOX treated 4T1 cells, obvious nuclei accumulation of DOX was found after 6 h co-incubation. At 12 h time point, bright blue spots stained with Hoechst-33342 were observed in the cellular nuclei, which became more notable post 24 h co-incubation, implying significant DNA damage and early apoptosis of 4T1 cells since Hoechst-33342 can stain condensed chromatin DNA in apoptotic cells more brightly than that in normal cells [22]. In contrast, only slight DNA damage was found after 24 h co-incubation with free DOX or DNA-DOX complexes ( Figure SI5).…”
Section: Intracellular Gnr@dox Uptake and Distributionmentioning
confidence: 97%
“…When the cells were treated with GNR@DOX and then irradiated with NIR laser for 6 min, 90% of 4T1 cells lost their viability, significant higher than the cells treated with free DOX or GNR-DNA plus laser irradiation. The laser irradiation induced phototoxicity was further visualized with live-dead-apoptotic staining assay as described in our previous study [22]. Calcein-AM used for the staining assay can only be activated in live cells to produce green fluorescence.…”
Section: Phototoxicity Assay In Vitromentioning
confidence: 99%
“…These oxides possess not only excellent electronic transport properties due to their unique crystal structure [1], but also technical applications in electrochromic devices [2][3], humidity sensors [4], photocatalyst devices [5], etc. In recent years, it has been reported that cesium tungsten bronze (Cs 0.33 WO 3 ) exhibits higher visible transparency and broad waveband absorption (800-15,000 nm) [6], which have potential applications in the field of heat insulating film [7] and photothermal ablation therapy [8]. Guo et al [9] and our previous research [10] reported that Cs x WO 3 particles could be successfully prepared by solvothermal process using CsOH and WCl 6 as raw materials; however these raw materials are not environmental friendly.…”
Section: Introductionmentioning
confidence: 99%